Pengelolaan Media Informasi dalam Pembelajaran untuk Penguatan Perilaku Religiusitas Siswa di Sekolah Dasar - Yosefo Gule; Antonia Junianty laratmase; Sofia F Rahmani; Choirus Sholihin; Rinda Riztya (Departement of Mathematics Education, 2023)
This study aims to carry out research and elaboration regarding how to manage information media in learning to strengthen the religious behavior of students in elementary schools. This study uses the method of literature review or content analysis. The results of this study show that it is important for school heads and teachers to make careful planning in every decision related to school programs. Then it is important for the principal to shape the image of the school by improvising the vision and mission made by the principal which puts forward various religious character values ​​in school activities. It is better if all teachers are given responsibility by the school principal in developing students' abilities and religious character so that whatever subject is always associated with various religious values ​​that make students more obedient and well-behaved. It is better if the principal and teacher carry out an evaluation and make a small note that assesses the daily life of students at school as evaluation material and also as a reference for carrying out more mature planning in developing students' religious character.